Islamic Economic View of On-Line Buying and Selling Using a Cash On Delivery System - saleng, Saleng (Zabags International Journal of Economy, 2023)
In this research the author found an interesting fact that society Talang Babat Tengah sub-district has active participation in running the business small by using a gadget or Android cellphone for transactions to increase the family economy. This business is one of the businesses current affairs that have a positive impact on people's income, especially in conditions facing the Covid-19 pandemic like this. Therefore The author is curious about this if viewed from Islamic/Shari'ah economics. Objective The purpose of this research is to find out the mechanism of online buying and selling implement a COD system. Apart from that, the aim is to find out how Islamic economic views on online buying and selling mechanisms by implementing the COD system. Meanwhile, the research method used is methodqualitative with a case study approach. The aim of qualitative research itself is to provide a systematic, normative and accurate description of existing phenomena, or the relationships between the phenomena being studied as they are without special treatment. The data source in this research is the data source Primary and secondary related to this research include the community and perpetrators ol-shop. The discussion and results of this research are viewed from the perspective aspect Islamic economics towards online buying and selling mechanisms that use a system order then if the ordered goods have arrived then the buyer will do it payment settlement (COD “cash on delivery”) and this can be categorized or categorized equate it with the As-Salam Agreement and the Istisnha Agreement.